Rad4 mainly functions in Chk1-mediated DNA damage checkpoint pathway as a scaffold protein in the fission yeast Schizosaccharomyces pombe. - Ming Yue; Li Zeng; Amanpreet Singh; Yongjie Xu (PLoS ONE, 2014)
Rad4/Cut5 is a scaffold protein in the Chk1-mediated DNA damage checkpoint in S. pombe. However, whether it contains a robust ATR-activation domain (AAD) required for checkpoint signaling like its orthologs TopBP1 in humans and Dpb11 in budding yeast has been incompletely clear. To identify the putative AAD in Rad4, we carried out an extensive genetic screen looking for novel mutants with an enhanced sensitivity to replication stress or DNA damage in which the function of the AAD can be eliminated by the mutations. Two new mutations near the N-terminus were identified that caused significantly higher sensitivities to DNA damage or chronic replication stress than all previously reported mutants, suggesting that most of the checkpoint function of the protein is eliminated. However, these mutations did not affect the activation of Rad3 (ATR in humans) yet eliminated the scaffolding function of the protein required for the activation of Chk1. Several mutations were also identified in or near the recently reported AAD in the C-terminus of Rad4. However, all mutations in the C-terminus only slightly sensitized the cells to DNA damage. Interestingly, a mutant lacking the whole C-terminus was found resistant to DNA damage and replication stress almost like the wild type cells. Consistent with the resistance, all known Rad3 dependent phosphorylations of checkpoint proteins remained intact in the C-terminal deletion mutant, indicating that unlike that in Dpb11, the C-terminus of Rad4 does not contain a robust AAD. These results, together with those from the biochemical studies, show that Rad4 mainly functions as a scaffold protein in the Chk1, not the Cds1(CHK2 in humans), checkpoint pathway. It plays a minor role or is functionally redundant with an unknown factor in Rad3 activation.